2015
DOI: 10.1016/j.molmet.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

High intensity interval training improves liver and adipose tissue insulin sensitivity

Abstract: ObjectiveEndurance exercise training reduces insulin resistance, adipose tissue inflammation and non-alcoholic fatty liver disease (NAFLD), an effect often associated with modest weight loss. Recent studies have indicated that high-intensity interval training (HIIT) lowers blood glucose in individuals with type 2 diabetes independently of weight loss; however, the organs affected and mechanisms mediating the glucose lowering effects are not known. Intense exercise increases phosphorylation and inhibition of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 76 publications
(115 reference statements)
6
71
2
7
Order By: Relevance
“…In these studies [31,32] PT began with the start of the diet for development of MS. Few studies [1,18] have evaluated PT as a treatment of already established MS. These studies show that PT induces a reduction in systolic blood pressure, together with increased sensitivity to insulin and in the gene expression of GLUT4 in white adipose tissue and gastrocnemius muscle [1], and reduces retroperitoneal and epididymal fat [18,33]. In our present study, PT should be considered a treatment because it started in the last 6 weeks of the diets, and therefore with an already established MS disorder, as shown through the increased MAP, HR and body mass of the rats.…”
Section: Discussionmentioning
confidence: 80%
“…In these studies [31,32] PT began with the start of the diet for development of MS. Few studies [1,18] have evaluated PT as a treatment of already established MS. These studies show that PT induces a reduction in systolic blood pressure, together with increased sensitivity to insulin and in the gene expression of GLUT4 in white adipose tissue and gastrocnemius muscle [1], and reduces retroperitoneal and epididymal fat [18,33]. In our present study, PT should be considered a treatment because it started in the last 6 weeks of the diets, and therefore with an already established MS disorder, as shown through the increased MAP, HR and body mass of the rats.…”
Section: Discussionmentioning
confidence: 80%
“…2, D-F). We (38) recently demonstrated that this HIIT exercise protocol increased oxygen consumption (V O 2 ), carbon dioxide consumption (V CO 2 ), respiratory exchange ratio (RER), food intake, and water intake in HFD-fed mice. We also published that this HIIT exercise protocol does not alter body mass, whole body adiposity, adipose mass, liver mass, or heart mass (38).…”
Section: Resultsmentioning
confidence: 99%
“…After a 3-day acclimation to treadmill running (19), exercise capacity was measured using a graded exercise test during which mice began running at 8 m/min on a 5% grade and treadmill speed was gradually increased by 1 m/min every 2 min until exhaustion, as described previously (38,54). This test was also repeated after 6 wk of exercise training, which involved treadmill running 3 days per week for 1 h each day, as previously described (38). Specifically, the treadmill running involved running for 2 min at 17 m/min at a 5% grade (100% of average pretrained maximal running speed/exercise capacity) and then resting for 2 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have looked into the effect of intermittent training on total cholesterol, HDL-C, LDL-C, TG (30)(31)(32)(33)(34)(35)53) or VLDL, HDL and LDL lipoprotein particles (36). HIIT was shown to activate AMP-activated protein kinase (AMPK) and p38 mitogen-activated protein kinase (MAPK), thereby increasing the capacity for glucose and fatty acid oxidation (54,55). The studies that examined the effect of intermittent training on plasma lipids or lipoproteins provided equivocal results, however; they differ largely with respect to training protocols (sprint, ergometer cycling, intensity, interval length from 8 s to 6 min, work : rest ratio), duration (from 8 wk to 18 mo), subjects investigated (usually sedentary individuals with comorbidities such as metabolic syndrome, obesity, essential hypertension), baseline lipid levels and work-to-rest ratio.…”
Section: Discussionmentioning
confidence: 99%